2011
DOI: 10.1016/j.ejps.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated destabilization and drug release from liposomes comprising dioleoylphosphatidylethanolamine

Abstract: Liposomal encapsulation of doxorubicin (DXR) improves tumor accumulation and reduces adverse effects. One possible strategy for further optimization of this delivery technology would be to design the liposome carrier to release its content within the tumor tissue in response to specific stimuli such as ultrasound (US). In this study, the tumor uptake properties and therapeutic efficacy of 1,2 distearoyl-sn-glycero-3-phosphatidylethanolamine-based liposomes containing DXR were investigated in nude mice bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 48 publications
(38 reference statements)
0
34
0
Order By: Relevance
“…We recently demonstrated that incorporation of DOPE into liposome bilayers drastically enhanced sonosensitivity compared to DSPE-based liposomes and standard liposomal DXR, respectively (Evjen et al, 2011a). The minimum amount of DOPE required for maintaining an acceptable sonosensitivity in vitro, however, was not explored.…”
Section: Effect Of Dope Level On Sonosensitivitymentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that incorporation of DOPE into liposome bilayers drastically enhanced sonosensitivity compared to DSPE-based liposomes and standard liposomal DXR, respectively (Evjen et al, 2011a). The minimum amount of DOPE required for maintaining an acceptable sonosensitivity in vitro, however, was not explored.…”
Section: Effect Of Dope Level On Sonosensitivitymentioning
confidence: 99%
“…DXR was remote loaded into liposomes using an ammonium sulfate transmembrane gradient (Haran et al, 1993), as previously described by Evjen et al, 2011a. The resulting nominal lipid and DXR concentrations were 16 mg/ml and 1 mg/ml, respectively.…”
Section: Liposome Preparationmentioning
confidence: 99%
See 3 more Smart Citations